Operation Fix Marabelle - Parent, Nancy; Disney Storybook Artists (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2020)
Fancy Nancy discovers a new talent for repairing broken toys in her neighborhood, but she must learn to keep her cool when her next patient is her beloved doll Marabelle.
Keywords: Fancy Nancy -- (Fictitious character) -- Juvenile fiction; Fancy Nancy -- (Fictitious character) -- Fiction; Dolls -- Juvenile fiction; Physicians -- Juvenile fiction; Dolls -- Fiction; Physicians -- Fiction